2020
DOI: 10.1200/jco.19.02677
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Physical Activity and Future Neurocognitive Problems in Adult Survivors of Childhood Cancers: A Report From the Childhood Cancer Survivor Study

Abstract: PURPOSE To investigate longitudinal associations between physical activity (PA) and neurocognitive problems in adult survivors of childhood cancer. METHODS A total of 12,123 5-year survivors diagnosed between 1970 and 1999 (median [range] age at diagnosis, 7 [0-21] years, time since diagnosis at baseline, 16 [6-30] years) and 720 siblings self-reported PA and neurocognitive problems. PA was collected at baseline, and PA and neurocognitive data were obtained 7 (1-12) years and 12 (9-14) years later. PA consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 53 publications
2
31
1
Order By: Relevance
“…For adolescents especially, the benefits of engaging in sports might include regaining a sense of having a lively, properly-functioning body, enhancing relationship with peers and a spirit of independence. These findings are in line with research demonstrating positive relationships between physical activity and cognitive outcomes ( 25 27 , 37 ). We know that adolescents with cancer are less active than their healthy peers (especially when in hospital), and that fatigue is more prevalent in this age group than in children, and might be particularly distressing ( 20 , 38 ).…”
Section: Lessons Learned and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For adolescents especially, the benefits of engaging in sports might include regaining a sense of having a lively, properly-functioning body, enhancing relationship with peers and a spirit of independence. These findings are in line with research demonstrating positive relationships between physical activity and cognitive outcomes ( 25 27 , 37 ). We know that adolescents with cancer are less active than their healthy peers (especially when in hospital), and that fatigue is more prevalent in this age group than in children, and might be particularly distressing ( 20 , 38 ).…”
Section: Lessons Learned and Discussionsupporting
confidence: 91%
“…Physical activity has favorable effects on various levels of functioning in individuals during and after their treatment for cancer, encompassing aspects of QoL, mood symptoms, fitness level, muscle strength, body composition, and active attainment of social roles ( 5 , 7 , 8 , 12 , 25 , 31 , 32 ). A possible relationship between fitness level and the risk of mortality ( 4 ) and tumor recurrence ( 11 , 33 ) has also emerged, and is worth exploring further.…”
Section: Lessons Learned and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Affected patients experienced difficulty resuming pre-cancer responsibilities and activities, which could negatively impact their quality of life. 5 , 6 In managing CRCI, non-pharmacological interventions such as physical activity 7 and cognitive rehabilitative program 8 were shown to improve patients’ psychosocial functioning and neurocognitive performance. However, effective pharmacological treatments for CRCI short- and long-term after cessation of cancer therapy are lacking in view of the poor understanding of the underlying pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggested that the safety and feasibility of lifestyle interventions are significant if introduced while patients are receiving cancer treatment [ 170 ]. Most of the lifestyle interventions in CCS are focused on behavioral interventions in healthy aging like nonsmoking, caloric restriction, and physical activity [ 171 ]. A study demonstrated that both nutrition and physical activity are necessary to counteract the early onset of obesity and chronic diseases in CCS [ 172 , 173 ].…”
Section: Health and Management Tips For Childhood Cancer Survivorsmentioning
confidence: 99%